DINAMIKA USAHA PENGGILINGAN PADI KECIL DI MASA PANDEMI COVID-19 : STUDI KASUS KECAMATAN PURBARATU, KOTA TASIKMALAYA - Nisrina Guzmarani; Mahra Arari Heryanto; Elly Rasmikayati; Trisna Insan Noor (Universitas Galuh Ciamis, 2021)
The existence of the Covid-19 pandemic in Indonesia has had an impact on the Small Rice Milling Unit (Small RMU). With the massive assistance given at the beginning of the pandemic to help the community and to reduce the spread of Covid-19, causing RMU complain about a decline in income of more than 50%. Systems thinking approach is used to describe the dynamics. To describe the relationship, a Causal Loop Diagram (CLD) is used. While To identify problems and see behavior, one of PRA (Participatory Rural Appraisal) techniques is used, using a trend chart. A model formulation stage, content analysis is used. The results showed that the decrease in income that RMU complained about loss of a large amount of revenue from rice production activities. However, if viewed from the side of overall income, RMU is actually experiencing an increase in income caused by makloon activities and drying floor rentals due to the harvest season in that time span. The existence of these two activities allows RMU to survive during the pandemic.